Pengembangan Standard Empiris Efikasi Penerangan Listrik Untuk Mendukung Perhitungan Cepat Dalam Perancangan Instalasi Listrik - Tiyono (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
In the process of drafting/design of electrical installations, especially in the design calculations required the installation of electric lighting fast, to soon be able to provide information about the equipment, technology, power requirements and cost required. Standard empirical efficacy of electric lighting that matches the tropics, is required to support rapid decision-making calculations, can immediately provide information about the equipment, technology, power requirements and cost involved as well as the consideration of energy-saving insights along with the development of the concept of